BAGAIMANA TATA KELOLA INTERNAL PERUSAHAAN PERTAMBANGAN? - Khairiyani (Jurnal Akuntansi Multiparadigma, 2018)
Abstract: What is the Application of Internal Governance of Mining Companies? This research was made to contribute to the influence of internal governance on the value of mining companies. The method used in this research is regression analysis based on Structural Equation Modeling in mining companies in the 2014-2016 period. This study found that mining companies were very interested in by the institutional side. The company has implemented an ownership and management structure. In addition, the number of board of directors is able to increase the value of the company. This means that more directors will provide good supervision on the operational aspects of the company.